STUDI KASUS: UPAYA DALAM MENSTABILKAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TIPE II DI RUANGAN MAHAKAM RSUD INCHE ABDOEL MOEIS SAMARINDA - Muhammad Taufiq Zul Fahmi (Yayasan Pendidikan Medika Indonesia, 2022)
Introduction: Diabetes Mellitus is a condition where the pancreas is not able to produce enough insulin or a condition where the pancreas is not produced effectively by the body. Diabetes mellitus is fatal when the management is not appropriate so that it can cause death. Management of diabetes mellitus requires drug therapy and non-drug therapy. Purpose: The purpose of the author is to understand nursing care for patients with diabetes mellitus problems by taking therapeutic action by administering insulin injections of novorapid and lantus to decrease blood glucose levels. Method: The method used by the author is a descriptive method with case study exposure through a nursing care approach, namely assessment, nursing diagnosis enforcement, planning, implementation, and nursing evaluation. Results: 3x24 hour nursing actions for DM patients are hyperglycemia management to stabilize blood glucose levels, namely teaching how to regulate blood glucose levels, recommending eating patterns, teaching managing daily activities, and collaborative insulin administration. The problem of unstable blood glucose levels has been partially resolved so that it requires further treatment and collaboration, patients, and families is indispensable for the success of nursing care. Conclusion: It is hoped to increase knowledge of diabetes mellitus's patients who are no longer producing the insulin hormone well enough to administer insulin injections by themselves to stabilize blood glucose levels. Keywords: Diabetes Mellitus, Blood Glucose Level, Therapy Insulin